Exploring the pragmatics of 'Don't Look Up' movie script: An analysis of illocutionary acts - Ifttitach Khoirotun Nisa’; Cattleya Wahyu Pravitha (Universitas Merdeka Malang, 2023)
This study examines illocutionary acts in Adam McKay's film Don't Look Up. Randall and Kate, two amateur astronomers, are the main characters in this movie who make the startling discovery that a comet is heading straight for Earth, posing a catastrophic threat to all life on the planet. This study is intended to provide information about illocutionary acts found in the movie script of Don't Look Up. The writers employ a qualitative approach in studying the types of illocutionary acts found in “Don’t Look Up” movie script. The script consisted of 127 pages and all the pages are used as the data. The data collection procedures are first, read the movie script. Second, identified the utterances that contain illocutionary acts. Third, classified the utterances that are found in movie script based on the five types of illocutionary acts. The writers then analyzed the data by using the theory of Searle (1968) to explore the most found type of illocutionary act in the movie script. The writers concluded that this movie contains five types of illocutionary acts: 29 percent assertive, 19 percent directive, 5 percent commissive, 39 percent expressive, and 8 percent declarative. According to the data, the most common category found in this movie is expressive for many unexpected, sad, funny, annoying, romantic, and other expressive words are voiced in the movie script.